2019
DOI: 10.1177/0887302x19860913
|View full text |Cite
|
Sign up to set email alerts
|

Impact of External Knowledge Inflow on Product and Process Innovation of Korean SMEs: Absorptive Capacity as a Mediator

Abstract: We examine the role of external knowledge inflow in improving the product and process innovation of Korean exporting small- and medium-sized enterprises (SMEs) in the textiles, apparel, and footwear industries. Building on the resource-based view (RBV), we investigate how five sources of knowledge inflow (suppliers, customers, competitors, universities, and government agencies) contribute to product and process innovation through absorptive capacity (AC) as a mechanism to explain the link between external know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 51 publications
(77 reference statements)
3
14
0
1
Order By: Relevance
“…Namely, the heterogeneous knowledge obtained by knowledge search needs to be transferred into the internal knowledge base through a firm’s absorptive capacity. The vital role of AC between knowledge search and the innovative outcome has been proven by previous researches based on enterprise competence theory (Jeong et al , 2019; Aliasghar et al , 2019; Russo-Spena and Di Paola, 2019). This research merely provides complementary evidence from a large-scale sample of Chinese manufacturing firms.…”
Section: Discussionmentioning
confidence: 90%
“…Namely, the heterogeneous knowledge obtained by knowledge search needs to be transferred into the internal knowledge base through a firm’s absorptive capacity. The vital role of AC between knowledge search and the innovative outcome has been proven by previous researches based on enterprise competence theory (Jeong et al , 2019; Aliasghar et al , 2019; Russo-Spena and Di Paola, 2019). This research merely provides complementary evidence from a large-scale sample of Chinese manufacturing firms.…”
Section: Discussionmentioning
confidence: 90%
“…According to table 1, previous studies found a positive relationship between inbound innovation and FP (Aliasghar et al, 2019;Jeong et al, 2019;Lazzarotti et al, 2017;Lorenz et al, 2020;Lu et al, 2021). As well, some scholars demonstrated that inbound and outbound innovation positively relates to FP (Burcharth et al, 2017;Hou et al, 2019;Wang & Xu, 2018;Zhou et al, 2018).…”
Section: Research Findingsmentioning
confidence: 85%
“…This study has identified the areas that the previous researchers considered in OI studies during the last seven years. Most of the scholars have focused on absorptive capacity (Aliasghar et al, 2019;Flor et al, 2017;Jeong et al, 2019), knowledge attributes (Wang & Jiang, 2020;Xie et al, 2018;Zhou et al, 2019), human resource practices (Burcharth et al, 2017;Natalicchio et al, 2018) and different capabilities like alliance management capability (Cheng & Shiu, 2020), functional capability (Lu et al, 2021), organizational capability (Cheng & Shiu, 2015) with OI and FP. Organizational learning (Wang & Xu, 2018) and innovativeness (Bahemia et al, 2017) have also gained much attention in previous studies.…”
Section: Research Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, entrepreneurs can be inspired by these sources and implement innovations. This is important because research carried out in South Korea (which has a highly developed economy) confirms that the implementation of product and process innovations was influenced by customers, universities and government agencies (Jeong, Chung, Roh, 2019). In this context, it would be beneficial to repeat the study in a few years, so that further development in the use of sources can be reviewed.…”
Section: Discussionmentioning
confidence: 99%